Binder for secondary battery functional layer, slurry composition for secondary battery functional layer, functional layer for secondary battery, and secondary battery

By using a granular polymer containing acidic functional group monomer and reactive functional group monomer, the problem of insufficient heat shrinkage resistance and adhesion of the functional layer of the secondary battery is solved, and high stability and long-term performance maintenance of the functional layer are achieved.

CN119547264APending Publication Date: 2025-02-28ZEON CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380054942.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-07-18
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

There is room for improvement in the heat shrinkage resistance and adhesion of the functional layer of the existing secondary battery, and it is easily reduced after a long period of use.

Method used

A binder containing a granular polymer of specific composition and characteristics is used, and in particular, a granular polymer containing acidic functional group monomer and reactive functional group monomer is ensured that the membrane elastic modulus after the accelerated test is less than 10 MPa.

Benefits of technology

The thermal shrinkage resistance, adhesion and storage stability of the functional layer are greatly improved, ensuring that the secondary battery maintains excellent battery characteristics after long-term use.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The purpose of the present invention is to provide a binder for a functional layer of a secondary battery, said binder being capable of forming a functional layer having excellent heat shrinkage resistance, adhesiveness, and storage stability. The present invention provides a binder for a functional layer of a secondary battery, comprising a particulate polymer comprising an acidic functional group-containing monomer unit and a reactive functional group-containing monomer unit containing a functional group capable of reacting with the acidic functional group, the content ratio of the reactive functional group-containing monomer unit is 7-30% by mass (inclusive) when all of the monomer units included in the particulate polymer are taken as 100% by mass, and the elastic modulus of a film comprising the particulate polymer after an acceleration test is 10 MPa or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive for a secondary battery functional layer, a slurry composition for a secondary battery functional layer, a secondary battery functional layer and a secondary battery. Background Art

[0002] Secondary batteries such as lithium-ion secondary batteries are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and have been used in a wide range of applications. In addition, secondary batteries generally have battery components such as electrodes (positive and negative electrodes) and separators that separate the positive electrode from the negative electrode to prevent short circuits between the positive and negative electrodes.

[0003] Here, as the battery member of the secondary battery, a member having a functional layer is used. The functional layer includes a binder material and optionally particles (hereinafter referred to as "functional particles") blended in order to enable the battery member to exert a desired function.

[0004] Specifically, as a separator of a secondary battery, a separator having an adhesive layer containing an adhesive material and a porous membrane layer containing an adhesive material and non-conductive particles as functional particles on a separator substrate is used. In addition, as an electrode of a secondary battery, an electrode having the above-mentioned adhesive layer and porous membrane layer on an electrode substrate is used, and the above-mentioned electrode substrate is formed by arranging an electrode composite material layer on a current collector.

[0005] Moreover, in order to achieve further performance improvement of secondary batteries, in the past, attempts have been made to improve the adhesive material. For example, in patent document 1, a non-aqueous secondary battery functional layer adhesive is disclosed, which includes a granular polymer, wherein the granular polymer contains (meth) alkyl acrylate monomer units, aromatic monovinyl monomer units, epoxy / N-methylol crosslinking monomer units and polyethylenically unsaturated crosslinking monomer units in a specified ratio, and the swelling degree of the granular polymer in the non-aqueous electrolyte is within a specified range. Moreover, according to patent document 1, by using the adhesive, a functional layer with excellent adhesion before and after electrolyte immersion can be formed, and the life characteristics of the non-aqueous secondary battery having the functional layer can also be improved.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent document 1: Japanese Patent No. 6515574. Summary of the invention

[0009] Problem that the invention aims to solve

[0010] The functional layer formed using the above-mentioned prior art adhesive has room for improvement in terms of heat shrinkage resistance.

[0011] Furthermore, regarding the functional layer formed using the above-mentioned conventional adhesive, there is room for further improvement in the adhesiveness of the functional layer.

[0012] Furthermore, the functional layer formed using the adhesive is also required to be less likely to deteriorate in heat shrinkage resistance and adhesiveness even over a long period of time, in other words, to have excellent storage stability.

[0013] Therefore, an object of the present invention is to provide a binder for a secondary battery functional layer capable of forming a functional layer having excellent heat shrinkage resistance, adhesion and storage stability.

[0014] Another object of the present invention is to provide a slurry composition for a secondary battery functional layer capable of forming a functional layer having excellent heat shrinkage resistance, adhesiveness, and storage stability.

[0015] Another object of the present invention is to provide a functional layer for a secondary battery having excellent heat shrinkage resistance, adhesiveness, and storage stability.

[0016] Another object of the present invention is to provide a secondary battery having the functional layer.

[0017] Solutions for solving problems

[0018] The present inventors have conducted intensive studies for the purpose of solving the above problems. Then, the present inventors have newly found that the above problems can be solved by using a binder containing a particulate polymer having a predetermined composition and properties, thereby completing the present invention.

[0019] That is, the object of the present invention is to advantageously solve the above-mentioned problems. [1] The present invention is a binder for a secondary battery functional layer, which comprises a granular polymer, wherein the granular polymer comprises an acidic functional group-containing monomer unit and a reactive functional group-containing monomer unit containing a functional group capable of reacting with the acidic functional group, wherein the content of the reactive functional group-containing monomer unit is greater than 7% by mass and less than 30% by mass, when all the monomer units contained in the granular polymer are taken as 100% by mass, and the elastic modulus of a film formed by the granular polymer after an accelerated test is less than 10 MPa.

[0020] The above-described binder for a secondary battery functional layer can form a functional layer having excellent heat shrinkage resistance, adhesiveness, and storage stability.

[0021] In the present specification, “comprising a monomer unit” means “a polymer obtained using the monomer contains a repeating unit derived from the monomer”.

[0022] In this specification, the "content ratio (mass %) of each monomer unit (each repeating unit) contained in the polymer can be expressed as 1 H-NMR, 13 The determination is carried out by nuclear magnetic resonance (NMR) methods such as C-NMR. In addition, for monomer units containing acidic functional groups, the nuclear magnetic resonance (NMR) method is used to determine the type (qualitative), and the content ratio of monomer units containing acidic functional groups contained in the polymer is determined by conductivity titration (quantitative). In the conductivity titration method, the secondary battery functional layer is diluted with a binder to an appropriate concentration, and titrated with sodium hydroxide aqueous solution and hydrochloric acid aqueous solution, thereby determining the acid amount.

[0023] In the present specification, examples of the "functional group capable of reacting with an acidic functional group" include a cyclic ether group, a hydroxyl group, and an amide group.

[0024] In the present specification, the elastic modulus of a film composed of a particulate polymer after an accelerated test can be measured according to the procedure and method described in Examples.

[0025] [2] In the binder for a secondary battery functional layer of [1], preferably, the content ratio of the acidic functional group-containing monomer unit is 0.1% by mass or more and 1% by mass or less, based on 100% by mass of all monomer units contained in the particulate polymer.

[0026] When the content ratio of the acidic functional group-containing monomer unit is not less than the above lower limit, based on 100% by mass of all monomer units contained in the particulate polymer, the particulate polymer can be easily produced and the storage stability of the functional layer can be improved.

[0027] On the other hand, when the content ratio of the acidic functional group-containing monomer unit is not more than the above upper limit, when all monomer units contained in the particulate polymer are taken as 100 mass %, the storage stability of the functional layer can be improved.

[0028] [3] In the binder for secondary battery functional layer of the above-mentioned [1] or [2], it is preferred that the above-mentioned granular polymer further contains a cross-linking monomer unit, and when all the monomer units contained in the above-mentioned granular polymer are taken as 100 mass %, the content ratio of the above-mentioned cross-linking monomer unit is greater than 0 mass % and is less than 1.5 mass %.

[0029] When all monomer units contained in the particulate polymer are taken as 100 mass %, if the content ratio of the crosslinkable monomer unit is more than the above lower limit, the cycle characteristics of the secondary battery can be improved.

[0030] On the other hand, when all monomer units contained in the particulate polymer are taken as 100 mass %, if the content ratio of the crosslinkable monomer unit is not more than the above upper limit, the adhesiveness of the functional layer can be improved.

[0031] [4] In the binder for secondary battery functional layer of any one of [1] to [3] above, it is preferred that the granular polymer further comprises a cyano group-containing monomer unit, and when all monomer units contained in the granular polymer are taken as 100% by mass, the content ratio of the cyano group-containing monomer unit is greater than 2% by mass and less than 30% by mass.

[0032] When the content ratio of the cyano group-containing monomer unit is not less than the above lower limit, the adhesiveness of the functional layer can be improved, based on the fact that all monomer units contained in the particulate polymer are 100% by mass.

[0033] On the other hand, when all monomer units contained in the particulate polymer are taken as 100 mass %, if the content ratio of the cyano group-containing monomer units is not more than the above upper limit, the cycle characteristics of the secondary battery can be improved.

[0034] [5] The binder for a secondary battery functional layer according to any one of [1] to [4] above preferably contains water and has a pH of 4 or more and 8 or less.

[0035] When the pH of the binder for a secondary battery functional layer is within the above range, the storage stability of the functional layer can be improved.

[0036] In this specification, the pH of the binder for a secondary battery functional layer can be measured by the method described in Examples.

[0037] [6] In the binder for a secondary battery functional layer according to any one of [1] to [5] above, the particulate polymer preferably has a glass transition temperature of 20° C. or less.

[0038] When the glass transition temperature of the particulate polymer is at most the above upper limit, the adhesiveness of the functional layer can be improved.

[0039] In the present specification, the “glass transition temperature” of the particulate polymer can be measured using the method described in Examples of the present specification.

[0040] [7] In the binder for a secondary battery functional layer according to any one of [1] to [6] above, the volume average particle size of the particulate polymer is preferably 0.1 μm or more and 0.2 μm or less.

[0041] When the volume average particle size of the particulate polymer is not less than the above lower limit, the cycle characteristics of the secondary battery can be improved.

[0042] On the other hand, when the volume average particle size of the particulate polymer is not more than the above upper limit, the adhesiveness of the functional layer can be improved.

[0043] In this specification, the “volume average particle size” refers to a particle size at which the cumulative volume calculated from the smaller particle size side accounts for 50% in a particle size distribution (volume basis) measured by a laser diffraction method.

[0044] [8] In the binder for a secondary battery functional layer according to any one of [1] to [7] above, the degree of swelling of the particulate polymer with respect to an electrolyte solution is preferably 3 times or more and 5 times or less.

[0045] When the degree of swelling of the particulate polymer with the electrolyte is not less than the above lower limit, the adhesiveness of the functional layer can be improved.

[0046] On the other hand, when the degree of swelling of the particulate polymer with the electrolyte is not more than the above upper limit, the cycle characteristics of the secondary battery can be improved.

[0047] In the present specification, the "electrolyte swelling degree" of a granular polymer can be calculated as the value (unit: times) obtained by dividing the weight of a film (binder film) formed by the granular polymer after immersion by the weight before immersion when the film is immersed in a specific non-aqueous electrolyte under specified conditions. Specifically, the binder film can be formed using the method described in the examples of the present specification and measured using the measurement method described in the same example.

[0048] In addition, the present invention aims to advantageously solve the above-mentioned problems. [9] The present invention is a slurry composition for a secondary battery functional layer, which comprises the binder for a secondary battery functional layer according to any one of [1] to [8] and functional particles.

[0049] The slurry composition described above can form a functional layer having excellent heat shrinkage resistance, adhesiveness, and storage stability.

[0050]

[10] In the slurry composition for a secondary battery functional layer according to [9] above, it is preferred that the functional particles include non-conductive particles.

[0051] The slurry composition for a secondary battery functional layer containing non-conductive particles as functional particles can be suitably used to form a porous membrane layer.

[0052]

[11] In the slurry composition for a secondary battery functional layer of the above

[10] , it is preferred that the ratio of the volume average particle size of the non-conductive particles to the volume average particle size of the particulate polymer is 2.0 times or more and 7.0 times or less.

[0053] When the ratio of the volume average particle size of the non-conductive particles to the volume average particle size of the particulate polymer is equal to or greater than the above lower limit, the adhesiveness of the functional layer can be further improved.

[0054] On the other hand, when the ratio of the volume average particle size of the non-conductive particles to the volume average particle size of the particulate polymer is below the upper limit, the heat shrinkage resistance of the functional layer can be further improved. In addition, the cycle characteristics of the secondary battery can be further improved.

[0055] Furthermore, the present invention aims to advantageously solve the above-mentioned problems.

[12] The present invention is a secondary battery functional layer formed using the slurry composition for a secondary battery functional layer according to any one of [9] to

[11] .

[0056] The functional layer for a secondary battery is excellent in heat shrinkage resistance, adhesiveness, and storage stability.

[0057] Furthermore, the present invention aims to advantageously solve the above-mentioned problems.

[13] The present invention is a secondary battery having the secondary battery functional layer of

[12] above.

[0058] The above-mentioned secondary battery can exhibit excellent battery characteristics.

[0059] Effects of the Invention

[0060] According to the present invention, it is possible to provide a binder for a secondary battery functional layer capable of forming a functional layer having excellent heat shrinkage resistance, adhesiveness, and storage stability.

[0061] Furthermore, according to the present invention, it is possible to provide a slurry composition for a secondary battery functional layer capable of forming a functional layer having excellent heat shrinkage resistance, adhesiveness, and storage stability.

[0062] Furthermore, according to the present invention, a functional layer for a secondary battery having excellent heat shrinkage resistance, adhesiveness, and storage stability can be provided.

[0063] Furthermore, according to the present invention, a secondary battery having the functional layer can be provided. DETAILED DESCRIPTION

[0064] Hereinafter, embodiments of the present invention will be described in detail.

[0065] Here, the binder for the functional layer of the secondary battery of the present invention (hereinafter sometimes referred to as "binder") is used in the secondary battery for the manufacture of any functional layer that has the functions of reinforcement or bonding. For example, the binder of the present invention can be used to prepare the slurry composition for the functional layer of the secondary battery of the present invention (hereinafter sometimes referred to as "slurry composition"). Moreover, the slurry composition of the present invention can be used to form the above-mentioned functional layer. Furthermore, the functional layer for the secondary battery of the present invention (hereinafter sometimes referred to as "functional layer") is formed by the slurry composition of the present invention. Moreover, the secondary battery of the present invention has the functional layer of the present invention. For example, the secondary battery of the present invention has a positive electrode, a negative electrode and a separator as battery components, and at least one of the above-mentioned battery components has the functional layer of the present invention. That is, the secondary battery of the present invention has a battery component, which is a battery component having the functional layer of the present invention.

[0066] (Adhesive for secondary battery functional layer)

[0067] The binder of the present invention comprises a granular polymer having a prescribed composition and characteristics as described in detail below. In addition, the binder of the present invention is usually a composition in which the granular polymer is dispersed in a solvent such as water. In addition, the binder of the present invention may further contain components other than the granular polymer and the solvent (hereinafter referred to as "other components").

[0068] <Particle polymer>

[0069] The particulate polymer is a component that functions as a binder, imparts adhesiveness to the functional layer formed using the slurry composition containing the binder, and prevents components contained in the functional layer (for example, functional particles such as non-conductive particles) from being separated from the functional layer.

[0070] Here, the above-mentioned granular polymer includes an acidic functional group-containing monomer unit and a reactive functional group-containing monomer (hereinafter sometimes referred to as "reactive functional group-containing monomer") unit containing a functional group capable of reacting with the acidic functional group, and when all repeating units (all monomer units) contained in the granular polymer are taken as 100% by mass, the reactive functional group-containing monomer unit contains a proportion of 7% by mass or more and 30% by mass or less. In addition, in addition to the acidic functional group-containing monomer unit and the reactive functional group-containing monomer unit, the above-mentioned granular polymer may further contain other monomer units at will. As other monomer units, there are no particular restrictions, and cyano-containing monomer units, crosslinking monomer units, (meth) acrylate monomer units, etc. can be cited.

[0071] Furthermore, in the adhesive of the present invention, the elastic modulus of a film composed of the particulate polymer after an accelerated test is 10 MPa or less.

[0072] The adhesive of the present invention contains a particulate polymer having the above-mentioned composition and properties, and therefore can impart excellent heat shrinkage resistance, adhesion, and storage stability to the functional layer. The reason for this is not yet clear, but is presumed to be as follows.

[0073] First, it is presumed that the particulate polymer in the binder of the present invention has excellent particle stability because it contains an acidic functional group-containing monomer unit.

[0074] In addition, it is speculated that the granular polymer in the adhesive of the present invention contains a monomer unit containing a reactive functional group, so there are reactive functional groups on the surface of the particles. As a result, the reactive functional groups will form crosslinks or interact with the surface of the spacer substrate (for example, a surface hydrophilized by surface treatment) and other components contained in the functional layer. Moreover, it is speculated that by making the ratio of the monomer unit containing a reactive functional group contained in the granular polymer within the above-specified range, the above-mentioned crosslinks can be well formed or the above-mentioned interactions can be generated, thereby stabilizing the layer structure of the functional layer, and as a result, the heat shrinkage resistance and adhesion of the functional layer are improved.

[0075] Furthermore, the accelerated test of the granular polymer is a test in which the film is left to stand at 60°C for 14 days as shown in the examples described later. The results indicate that if the elastic modulus of the film composed of the granular polymer after such an accelerated test is 10 MPa or less, the number of crosslinks (degree of crosslinking) and the interaction with other components in the functional layer will be in a good state. In other words, the functional layer will remain in a stable state, thereby improving the storage stability.

[0076] Based on the above reasons, it is estimated that the adhesive of the present invention can impart excellent heat shrinkage resistance, adhesion, and storage stability to the functional layer.

[0077] <<Elastic modulus of film composed of granular polymer after accelerated test>>

[0078] In the adhesive of the present invention, the elastic modulus of the film composed of the particulate polymer after the accelerated test needs to be 10 MPa or less, preferably 7 MPa or less, and more preferably 5 MPa or less.

[0079] As described above, when the elastic modulus of the film composed of the particulate polymer after the accelerated test is not more than the above upper limit, the storage stability of the functional layer can be improved.

[0080] On the other hand, the elastic modulus of the film composed of the particulate polymer after the accelerated test is, for example, 0.1 MPa or more, 0.5 MPa or more, or 1 MPa or more.

[0081] In addition, the elastic modulus of the film composed of the particulate polymer after the accelerated test can be adjusted by changing the type and amount of the monomers used.

[0082] <<Elastic modulus of film composed of granular polymer before accelerated test>>

[0083] The elastic modulus of the film composed of the particulate polymer before the accelerated test is preferably 10 MPa or less, more preferably 7 MPa or less, further preferably 5 MPa or less, and further preferably 3 MPa or less.

[0084] On the other hand, the elastic modulus of the film composed of the particulate polymer before the accelerated test is, for example, 0.1 MPa or more, 0.5 MPa or more, or 1 MPa or more.

[0085] <<Composition of granular polymer>>

[0086] [Monomer units containing acidic functional groups]

[0087] Examples of the acidic functional group-containing monomer capable of forming the acidic functional group-containing monomer unit include a carboxyl group-containing monomer, a sulfonic acid group-containing monomer, and a phosphoric acid group-containing monomer.

[0088] Examples of the carboxyl group-containing monomer include monocarboxylic acids and derivatives thereof, dicarboxylic acids and anhydrides thereof, and derivatives thereof.

[0089] Examples of the monocarboxylic acid include acrylic acid, methacrylic acid, and crotonic acid.

[0090] Examples of the monocarboxylic acid derivative include 2-ethylacrylic acid, isocrotonic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, and α-chloro-β-E-methoxyacrylic acid.

[0091] Examples of the dicarboxylic acid include maleic acid, fumaric acid, and itaconic acid.

[0092] Examples of the dicarboxylic acid derivatives include maleic acid monoesters such as methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, and fluoroalkyl maleate.

[0093] Examples of the anhydride of dicarboxylic acid include maleic anhydride, acrylic anhydride, methylmaleic anhydride, and dimethylmaleic anhydride.

[0094] Furthermore, as the carboxyl group-containing monomer, an acid anhydride that generates a carboxyl group by hydrolysis can also be used.

[0095] Examples of the sulfonic acid group-containing monomer include vinyl sulfonic acid, methylvinyl sulfonic acid, (meth)allyl sulfonic acid, ethyl (meth)acrylate-2-sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid.

[0096] In addition, in this specification, "(meth)allyl" means allyl and / or methallyl, and "(meth)acrylic acid" means acrylic acid and / or methacrylic acid.

[0097] Examples of the phosphoric acid group-containing monomer include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate.

[0098] In addition, in this specification, "(meth)acryloyl group" means an acryloyl group and / or a methacryloyl group.

[0099] The above-mentioned acidic functional group-containing monomers may be used alone or in combination of two or more.

[0100] As the acidic functional group-containing monomer capable of forming the acidic functional group-containing monomer unit, from the viewpoint of further improving the particle stability of the granular polymer, it is preferred to use a carboxyl group-containing monomer, more preferably a monocarboxylic acid, further preferably at least one of acrylic acid and methacrylic acid, and further preferably acrylic acid.

[0101] That is, the particulate polymer preferably contains a carboxyl group-containing monomer unit, more preferably contains a monocarboxylic acid unit, further preferably contains at least one monomer unit of an acrylic acid unit and a methacrylic acid unit, and further preferably contains an acrylic acid unit.

[0102] When all repeating units (all monomer units) contained in the particulate polymer are taken as 100 mass %, the content ratio of the acidic functional group-containing monomer unit is preferably 0.1 mass % or more, preferably 1 mass % or less, more preferably 0.5 mass % or less, and further preferably 0.2 mass % or less.

[0103] When the content ratio of the acidic functional group-containing monomer unit is not less than the above lower limit, based on 100% by mass of all monomer units contained in the particulate polymer, the particulate polymer can be easily produced and the storage stability of the functional layer can be improved.

[0104] On the other hand, when the content ratio of the acidic functional group-containing monomer unit is not more than the above upper limit, when all monomer units contained in the particulate polymer are taken as 100 mass %, the storage stability of the functional layer can be improved.

[0105] [Monomer units containing reactive functional groups]

[0106] Examples of the reactive functional group-containing monomer that can form the reactive functional group-containing monomer unit include a cyclic ether group-containing monomer, a hydroxyl group-containing monomer, and an amide group-containing monomer.

[0107] The cyclic ether group-containing monomer is not particularly limited as long as it is a monomer containing a cyclic ether group, and examples thereof include monomers containing epoxy groups (epoxy rings) (epoxy group-containing monomers), monomers containing oxetane groups (oxetane rings) (oxetane group-containing monomers), etc. Among them, epoxy group-containing monomers are preferably used from the viewpoint of further improving the heat shrinkage resistance and adhesion of the functional layer.

[0108] Examples of the epoxy group-containing monomer include allyl glycidyl ether, glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl methacrylate, and 4-hydroxybutyl acrylate glycidyl ether.

[0109] Examples of the oxetane group-containing monomer include 3-((meth)acryloyloxymethyl)oxetane, 3-((meth)acryloyloxymethyl)-2-trifluoromethyloxetane, 3-((meth)acryloyloxymethyl)-2-phenyloxetane, 2-((meth)acryloyloxymethyl)oxetane, and 2-((meth)acryloyloxymethyl)-4-trifluoromethyloxetane.

[0110] In addition, in this specification, "(meth)acrylate" means acrylate and / or methacrylate.

[0111] As a hydroxyl group-containing monomer, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, etc. are mentioned, for example.

[0112] Examples of the amide group-containing monomer include N-vinylacetamide, (meth)acrylamide, dimethyl(meth)acrylamide, diethyl(meth)acrylamide, N-methoxymethyl(meth)acrylamide, and dimethylaminopropyl(meth)acrylamide.

[0113] In addition, as the reactive functional group-containing monomer, a monomer having two or more functional groups that can react with the acidic functional group can also be used, for example, a monomer containing a hydroxyl group and an amide group, etc. As the monomer containing a hydroxyl group and an amide group, N-hydroxymethyl (meth) acrylamide, hydroxyethyl (meth) acrylamide, etc. can be mentioned.

[0114] In addition, in the present specification, a monomer containing a hydroxyl group and an amide group is not included in the hydroxyl group-containing monomer, nor is it included in the amide group-containing monomer.

[0115] The reactive functional group-containing monomers listed above may be used alone or in combination of two or more.

[0116] As the reactive functional group-containing monomer capable of forming the reactive functional group-containing monomer unit, from the viewpoint of further improving the adhesion of the functional layer and, in particular, further improving the heat shrinkage resistance of the functional layer, it is preferred to use a cyclic ether group-containing monomer, it is preferred to use an epoxy group-containing monomer, it is further preferred to use at least one of allyl glycidyl ether and (meth) acrylate glycidyl ether, and it is further preferred to use at least one of allyl glycidyl ether and methacrylate glycidyl ether.

[0117] That is, the particulate polymer preferably contains a cyclic ether group-containing monomer unit, more preferably contains an epoxy group-containing monomer unit, further preferably contains at least any one of an allyl glycidyl ether unit and a glycidyl (meth)acrylate unit, and further preferably contains at least any one of an allyl glycidyl ether unit and a glycidyl methacrylate unit.

[0118] When all repeating units (all monomer units) contained in the granular polymer are taken as 100 mass %, the content ratio of the reactive functional group-containing monomer unit needs to be 7 mass % or more, preferably 10 mass % or more, more preferably 15 mass % or more, and further preferably 18 mass % or more, and needs to be 30 mass % or less, preferably 25 mass % or less, more preferably 22 mass % or less, and further preferably 20 mass % or less.

[0119] When the content ratio of the reactive functional group-containing monomer unit is not less than the above lower limit, the heat shrinkage resistance of the functional layer can be improved, based on 100% by mass of all monomer units contained in the particulate polymer.

[0120] On the other hand, when the content ratio of the reactive functional group-containing monomer unit is not more than the above upper limit, the adhesiveness of the functional layer can be improved when all the monomer units contained in the particulate polymer are taken as 100 mass %.

[0121] In one embodiment, the particulate polymer preferably contains two or more reactive functional group-containing monomer units, and more preferably contains a cyclic ether group-containing monomer unit and a hydroxyl group- and amide group-containing monomer unit.

[0122] In the case where the particulate polymer contains a cyclic ether group-containing monomer unit and a hydroxyl group- and amide group-containing monomer unit, when all repeating units (all monomer units) contained in the particulate polymer are taken as 100 mass %, the content ratio of the cyclic ether group-containing monomer unit is preferably 6.9 mass % or more, more preferably 9.5 mass % or more, further preferably 14.2 mass % or more, further preferably 17 mass % or more, preferably 25 mass % or less, more preferably 22 mass % or less, further preferably 19.5 mass % or less, further preferably 18.5 mass % or less.

[0123] When the content ratio of the cyclic ether group-containing monomer unit is not less than the above lower limit, the heat shrinkage resistance of the functional layer can be further improved, based on 100% by mass of all monomer units contained in the particulate polymer.

[0124] On the other hand, when the content ratio of the cyclic ether group-containing monomer unit is not more than the above upper limit, the adhesiveness of the functional layer can be further improved when all monomer units contained in the particulate polymer are taken as 100 mass %.

[0125] In the case where the granular polymer contains a cyclic ether group-containing monomer unit and a hydroxyl group- and amide group-containing monomer unit, when all repeating units (all monomer units) contained in the granular polymer are taken as 100 mass %, the content ratio of the hydroxyl group- and amide group-containing monomer unit is preferably 0.1 mass % or more, more preferably 0.5 mass % or more, further preferably 0.8 mass % or more, further preferably 1 mass % or more, preferably 5 mass % or less, more preferably 3 mass % or less, further preferably 2.5 mass % or less, further preferably 1.5 mass % or less.

[0126] When all monomer units contained in the particulate polymer are taken as 100 mass %, if the content ratio of the monomer units containing a hydroxyl group and an amide group is not less than the above lower limit, the heat shrinkage resistance of the functional layer can be further improved. In addition, the cycle characteristics of the secondary battery can be improved.

[0127] On the other hand, when the content ratio of the monomer units containing a hydroxyl group and an amide group is not more than the above upper limit, the adhesiveness of the functional layer can be further improved when all the monomer units contained in the particulate polymer are taken as 100 mass %.

[0128] Here, in the particulate polymer, the content ratio of the reactive functional group-containing monomer unit is preferably higher than the content ratio of the acidic functional group-containing monomer unit.

[0129] When the content ratio of the reactive functional group-containing monomer unit is higher than the content ratio of the acidic functional group-containing monomer unit, the heat shrinkage resistance and adhesiveness of the functional layer can be improved.

[0130] [Cyanide-containing monomer units]

[0131] In the present specification, a cyano group-containing monomer capable of forming a cyano group-containing monomer unit is not included in the above-mentioned acidic functional group-containing monomer and reactive functional group-containing monomer.

[0132] As the cyano group-containing monomer, (meth)acrylonitrile such as acrylonitrile and methacrylonitrile; α-halogenated acrylonitrile such as α-chloroacrylonitrile and α-bromoacrylonitrile; (meth)acrylic acid-2-ethyl ester such as 2-cyanoethyl acrylate and 2-cyanoethyl methacrylate; 2-cyanoethyl acrylamide, etc. These may be used alone or in combination of two or more in any ratio.

[0133] In addition, in this specification, "(meth)acrylonitrile" means acrylonitrile and / or methacrylonitrile.

[0134] As the cyano group-containing monomer capable of forming the cyano group-containing monomer unit, (meth)acrylonitrile is preferably used, and acrylonitrile is more preferably used, from the viewpoint of further improving the adhesiveness of the functional layer.

[0135] That is, the particulate polymer preferably contains a (meth)acrylonitrile unit, and more preferably contains an acrylonitrile unit.

[0136] When all repeating units (all monomer units) contained in the particulate polymer are taken as 100 mass %, the content ratio of the cyano group-containing monomer unit is preferably 2 mass % or more, more preferably 5 mass % or more, further preferably 8 mass % or more, preferably 30 mass % or less, more preferably 25 mass % or less, further preferably 15 mass % or less.

[0137] When the content ratio of the cyano group-containing monomer unit is not less than the above lower limit, the adhesiveness of the functional layer can be improved, based on the fact that all monomer units contained in the particulate polymer are 100% by mass.

[0138] On the other hand, when all monomer units contained in the particulate polymer are taken as 100 mass %, if the content ratio of the cyano group-containing monomer units is below the upper limit, the internal resistance of the secondary battery can be suppressed from increasing, and the cycle characteristics of the secondary battery can be improved.

[0139] [Crosslinking monomer unit]

[0140] The crosslinkable monomer capable of forming a crosslinkable monomer unit is a monomer capable of forming a crosslinked structure during or after polymerization by heating or irradiation with energy rays.

[0141] In the present specification, the crosslinking monomer is not included in the above-mentioned acidic functional group-containing monomer, reactive functional group-containing monomer and cyano group-containing monomer.

[0142] As crosslinking monomers, for example, multifunctional monomers having two or more polymerizable reactive groups in the monomer can be cited. As such multifunctional monomers, for example, divinyl monomers such as divinylbenzene, 1,3-butadiene, isoprene, and allyl methacrylate can be cited; di(meth)acrylic acid alkyl ester monomers such as ethylene dimethacrylate, diethylene glycol dimethacrylate, ethylene glycol dimethacrylate (EDMA), diethylene glycol diacrylate, and diacrylate-1,3-butylene glycol ester; tri(meth)acrylic acid alkyl ester monomers such as trimethylolpropane trimethacrylate and trimethylolpropane triacrylate can be cited. These can be used alone or in combination of two or more.

[0143] As the cross-linking monomer capable of forming the cross-linking monomer unit, from the viewpoint of improving the heat shrinkage resistance of the functional layer, at least one of allyl methacrylate and ethylene glycol dimethacrylate is preferably used. In addition, as the cross-linking monomer capable of forming the cross-linking monomer unit, from the viewpoint of improving the heat shrinkage resistance of the functional layer and improving the cycle characteristics of the secondary battery, allyl methacrylate is more preferably used.

[0144] That is, the particulate polymer preferably contains at least one monomer unit of an allyl methacrylate unit and an ethylene glycol dimethacrylate unit, and preferably contains an allyl methacrylate unit.

[0145] When all repeating units (all monomer units) contained in the particulate polymer are taken as 100 mass %, the content ratio of the crosslinkable monomer unit is preferably greater than 0 mass %, more preferably 0.3 mass % or more, preferably 1.5 mass % or less, more preferably 0.8 mass % or less.

[0146] When all monomer units contained in the particulate polymer are taken as 100 mass %, if the content ratio of the crosslinkable monomer unit is more than the above lower limit, the cycle characteristics of the secondary battery can be improved.

[0147] On the other hand, when all monomer units contained in the particulate polymer are taken as 100 mass %, if the content ratio of the crosslinkable monomer unit is not more than the above upper limit, the adhesiveness of the functional layer can be improved.

[0148] [(Meth)acrylate monomer unit]

[0149] In the present specification, the (meth)acrylate monomer capable of forming a (meth)acrylate monomer unit is not included in the above-mentioned acidic functional group-containing monomer, reactive functional group-containing monomer, cyano group-containing monomer and crosslinking monomer.

[0150] Examples of the (meth)acrylate monomer include an alkyl (meth)acrylate monomer and an aryl (meth)acrylate monomer. From the viewpoint of improving the adhesiveness of the functional layer, an alkyl (meth)acrylate monomer is preferred.

[0151] Examples of the (meth)acrylic acid alkyl ester monomer include: alkyl acrylates such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, tert-butyl acrylate, isobutyl acrylate, n-pentyl acrylate, isopentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, and stearyl acrylate; and alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, tert-butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, stearyl methacrylate, and glycidyl methacrylate. These may be used alone or in combination of two or more.

[0152] As the (meth)acrylic acid alkyl ester monomer, from the viewpoint of further improving the adhesiveness of the functional layer and improving the heat shrinkage resistance, it is preferable to use at least one of 2-ethylhexyl acrylate and butyl acrylate.

[0153] That is, the particulate polymer preferably contains at least one monomer unit of 2-ethylhexyl acrylate unit and butyl acrylate unit.

[0154] When all repeating units (all monomer units) contained in the particulate polymer are taken as 100 mass %, the content ratio of the (meth)acrylic acid ester monomer unit is preferably 40 mass % or more, more preferably 50 mass % or more, further preferably 60 mass % or more, preferably 90 mass % or less, more preferably 80 mass % or less, further preferably 75 mass % or less.

[0155] When the content ratio of the (meth)acrylic acid ester monomer unit is not less than the above lower limit, the adhesiveness of the functional layer can be improved when all monomer units contained in the particulate polymer are taken as 100 mass %.

[0156] On the other hand, when all monomer units contained in the particulate polymer are taken as 100 mass %, if the content ratio of the (meth)acrylate monomer units is below the upper limit, the heat shrinkage resistance of the functional layer can be improved. In addition, the cycle characteristics of the secondary battery can be improved.

[0157] <<Glass transition temperature of granular polymer>>

[0158] The glass transition temperature of the particulate polymer is preferably 20°C or lower, more preferably 10°C or lower, and further preferably 0°C or lower.

[0159] When the glass transition temperature of the particulate polymer is at most the above upper limit, the adhesiveness of the functional layer can be improved.

[0160] On the other hand, the lower limit of the glass transition temperature of the particulate polymer is not particularly limited, but is usually -100°C or higher.

[0161] <<Swelling degree of granular polymer in electrolyte>>

[0162] The degree of swelling of the particulate polymer with respect to the electrolyte is preferably 3 times or more, more preferably 3.5 times or more, and is preferably 5 times or less, more preferably 4.5 times or less.

[0163] When the degree of swelling of the particulate polymer with the electrolyte is not less than the above lower limit, the adhesiveness of the functional layer can be improved.

[0164] On the other hand, when the degree of swelling of the particulate polymer with the electrolyte is not more than the upper limit, an increase in the internal resistance of the secondary battery can be suppressed, thereby improving the cycle characteristics of the secondary battery.

[0165] The degree of swelling of the particulate polymer with the electrolyte can be adjusted by changing the type and amount of the monomers used and the conditions of the polymerization reaction (eg, polymerization temperature, polymerization reaction time, etc.).

[0166] <<Volume average particle size of granular polymer>>

[0167] The volume average particle size of the particulate polymer is preferably 0.1 μm or more, more preferably 0.12 μm or more, and is preferably 0.2 μm or less, more preferably 0.18 μm or less.

[0168] When the volume average particle size of the particulate polymer is not less than the above lower limit, the cycle characteristics of the secondary battery can be improved.

[0169] On the other hand, when the volume average particle size of the particulate polymer is not more than the above upper limit, the adhesiveness of the functional layer can be improved.

[0170] <<Structure of granular polymer>>

[0171] The structure of the particulate polymer is not particularly limited, and may be any of a block copolymer, a graft copolymer, a random copolymer, etc., and is preferably a random copolymer.

[0172] Furthermore, the particulate polymer may have a core-shell structure having a core portion and a shell portion covering at least a portion of the outer surface of the core portion, but preferably does not have a core-shell structure.

[0173] Therefore, the particulate polymer is particularly preferably a random copolymer having no core-shell structure.

[0174] In addition, in this specification, when the glass transition temperature of a particulate polymer is measured and only one glass transition temperature is detected, it is judged as a "random copolymer having no core-shell structure".

[0175] <<Preparation of granular polymer>>

[0176] The particulate polymer can be prepared by polymerizing a monomer composition containing the above-mentioned monomers.

[0177] Here, the content ratio of each monomer in the monomer composition is usually the same as the content ratio of the monomer unit in the desired particulate polymer.

[0178] The polymerization method of the particulate polymer is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. can be used. From the viewpoint of being able to easily adjust the volume average particle size of the particulate polymer, emulsion polymerization is preferred. As the polymerization reaction, addition polymerization such as ionic polymerization, free radical polymerization, and living free radical polymerization can be used. In addition, the emulsifier, dispersant, polymerization initiator, polymerization aid, etc. used in the polymerization can use those commonly used, and the amount used is also the amount commonly used.

[0179] When polymerizing the particulate polymer, it is preferred that the polymerization temperature be lower than the polymerization temperature at the start of the polymerization at any time from the start of the polymerization to the end of the polymerization to end the polymerization. The polymerization temperature at the end of the polymerization is preferably lower than the temperature at the start of the polymerization by 10° C. or more, more preferably lower by 15° C. or more. In addition, when lowering the polymerization temperature, a reducing agent such as ascorbic acid may be added.

[0180] <Solvent>

[0181] As the solvent that can be contained in the binder of the present invention, a known solvent that can disperse the above-mentioned granular polymer can be used. Among them, water is preferably used as the solvent. In addition, at least a part of the solvent that can be contained in the binder is not particularly limited, and can be a polymerization solvent for preparing the granular polymer.

[0182] <Solid content of binder for secondary battery functional layer>

[0183] The solid content of the binder (particulate polymer etc.) is preferably 30% by mass or more, more preferably 35% by mass or more, and is preferably 50% by mass or less, more preferably 45% by mass or less.

[0184] When the solid content of the binder is not less than the above lower limit, the particle stability of the particulate polymer can be improved, and as a result, the storage stability of the functional layer can be improved.

[0185] On the other hand, when the solid content of the binder is equal to or less than the above upper limit, it is possible to suppress excessive increase in the frequency of contact between particles, thereby improving the storage stability of the functional layer.

[0186] <pH of binder for secondary battery functional layer>

[0187] When water is used as the solvent, the pH of the binder is preferably 4 or higher, more preferably 5 or higher, and is preferably 8 or lower, more preferably 7 or lower.

[0188] When the pH of the binder is within the above range, the storage stability of the functional layer can be improved.

[0189] <Preparation of binder for secondary battery functional layer>

[0190] The preparation method of the binder of the present invention is not particularly limited. For example, when the granular polymer is prepared in a solvent such as water and the granular polymer is obtained in the form of a dispersion, the dispersion of the granular polymer can be used directly as the binder, or other components can be added to the dispersion of the granular polymer as the binder. Here, as other components, the "other components" described later in the "slurry composition for secondary battery functional layer" can be cited.

[0191] (Slurry composition for secondary battery functional layer)

[0192] The slurry composition of the present invention is a composition for forming a functional layer, comprising the above-mentioned binder and functional particles, and optionally further containing other components. That is, the slurry composition generally contains a granular polymer, a solvent and functional particles, and optionally further contains other components. Moreover, since the slurry composition of the present invention contains the above-mentioned binder, by drying the slurry composition of the present invention on, for example, a substrate, a functional layer having excellent heat shrinkage resistance, adhesion and storage stability can be obtained.

[0193] <Adhesive>

[0194] As the adhesive, the above-mentioned adhesive of the present invention is used.

[0195] In addition, the amount of the binder in the slurry composition is not particularly limited. The amount of the binder in the slurry composition is preferably 1 mass part or more, more preferably 1.5 mass parts or more, preferably 6 mass parts or less, and more preferably 3 mass parts or less relative to 100 mass parts of functional particles in terms of solid content.

[0196] When the amount of the binder in the slurry composition is not less than the above lower limit, the adhesiveness of the functional layer can be improved.

[0197] On the other hand, when the amount of the binder in the slurry composition is not more than the above upper limit, the heat shrinkage resistance of the functional layer can be improved.

[0198] <Functional particles>

[0199] Here, as the functional particles for causing the functional layer to exhibit a desired function, for example, when the functional layer is a porous membrane layer, non-conductive particles can be used.

[0200] In particular, since the functional layer formed using the slurry composition of the present invention has excellent heat shrinkage resistance, the slurry composition of the present invention containing non-conductive particles as functional particles can be suitably used to form a porous membrane layer for improving the heat resistance and strength of a battery member.

[0201] <<Non-conductive particles>>

[0202] As the non-conductive particles that can be used in the porous film layer of the secondary battery, there is no particular limitation, and both inorganic particles and organic particles can be used, and inorganic particles are generally used. Among them, as the material of the non-conductive particles, it is preferred that the material is stably present and electrochemically stable under the use environment of the secondary battery. From such a viewpoint, when the preferred examples of the material of the non-conductive particles are cited, oxide particles such as aluminum oxide (Alumina), hydrated aluminum oxide (boehmite), silicon oxide, magnesium oxide (Magnesia), calcium oxide, titanium oxide (Titania), BaTiO3, ZrO, aluminum oxide-silicon dioxide composite oxide, etc. can be cited; nitride particles such as aluminum nitride and boron nitride; covalent bond grains such as silicon and diamond; insoluble ionic grains such as barium sulfate, calcium fluoride, and barium fluoride; clay particles such as talc and montmorillonite, etc. In addition, these particles can be subjected to element replacement, surface treatment, solid solution, etc. as needed.

[0203] Moreover, as the material of the non-conductive particles, from the viewpoint of suppressing aggregation and improving the dispersibility of the slurry composition, it is preferred to use at least one non-conductive particle selected from alumina, boehmite and barium sulfate, and it is more preferred to use at least one non-conductive particle of alumina and barium sulfate.

[0204] The non-conductive particles may be used alone or in combination of two or more.

[0205] The volume average particle size of the non-conductive particles is preferably 0.1 μm or more, more preferably 0.3 μm or more, and is preferably 1.5 μm or less, more preferably 1.0 μm or less.

[0206] When the volume average particle size of the non-conductive particles is not less than the above lower limit, the adhesiveness of the functional layer can be improved.

[0207] On the other hand, when the volume average particle size of the non-conductive particles is equal to or less than the upper limit, the air permeability of the functional layer increases, so that the electrolyte injection property of the functional layer can be improved, and as a result, the cycle characteristics of the secondary battery can be improved.

[0208] Here, the ratio of the volume average particle size of the non-conductive particles to the volume average particle size of the granular polymer ("volume average particle size of the non-conductive particles" / "volume average particle size of the granular polymer") is preferably 2.0 times or more, more preferably 2.5 times or more, preferably 7.0 times or less, more preferably 5.0 times or less.

[0209] When the ratio of the volume average particle size of the non-conductive particles to the volume average particle size of the particulate polymer is equal to or greater than the above lower limit, the adhesiveness of the functional layer can be further improved.

[0210] On the other hand, when the ratio of the volume average particle size of the non-conductive particles to the volume average particle size of the particulate polymer is below the upper limit, the heat shrinkage resistance of the functional layer can be further improved. In addition, the cycle characteristics of the secondary battery can be further improved.

[0211] <Other ingredients>

[0212] The slurry composition may further include other components in addition to the above components. As long as the other components do not have an excessively negative impact on the battery reaction of the secondary battery having the functional layer, there is no particular restriction. In addition, the types of other components may be one or more than two.

[0213] Examples of other components include surfactants, wetting agents, leveling agents, dispersants, electrolyte decomposition inhibitors, and viscosity modifiers.

[0214] <<Viscosity regulator>>

[0215] Here, from the viewpoint of further improving the heat shrinkage resistance of the functional layer, it is preferred to use a viscosity modifier as another component. In addition, it is particularly preferred to use a water-soluble polymer as the viscosity modifier.

[0216] In the present specification, the polymer being "water-soluble" means that when 0.5 g of the polymer is dissolved in 100 g of water at a temperature of 25° C., the insoluble component is less than 1% by mass.

[0217] The water-soluble polymer is not particularly limited, but from the viewpoint of further improving the heat shrinkage resistance of the functional layer, it is preferable to use at least one of carboxymethyl cellulose and polyacrylamide.

[0218] The amount of the viscosity modifier in the slurry composition is not particularly limited. The amount of the water-soluble polymer in the slurry composition is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and preferably 3 parts by mass or less, more preferably 2 parts by mass or less, based on solid content relative to 100 parts by mass of the functional particles.

[0219] When the amount of the viscosity modifier in the slurry composition is not less than the above lower limit, the heat shrinkage resistance of the functional layer can be further improved.

[0220] On the other hand, when the amount of the viscosity modifier in the slurry composition is equal to or less than the upper limit, sufficiently high coating stability can be ensured when the slurry composition is applied to a substrate to form a functional layer.

[0221] <<Dispersant>>

[0222] In addition, from the viewpoint of improving the stability in the slurry composition, it is preferred to use a dispersant as another component. As the dispersant, there is no particular limitation, and for example, sodium polyacrylate, acrylic acid / sulfonic acid monomer copolymer sodium salt, etc. can be used. In addition, the dispersant is a component different from the above-mentioned viscosity modifier (water-soluble polymer, etc.).

[0223] The amount of the dispersant in the slurry composition is not particularly limited. The amount of the dispersant in the slurry composition is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, preferably 3 parts by mass or less, and more preferably 2 parts by mass or less, based on solid content relative to 100 parts by mass of the functional particles.

[0224] When the amount of the dispersant in the slurry composition is not less than the above lower limit, the stability of the slurry composition can be further improved.

[0225] On the other hand, when the amount of the dispersant in the slurry composition is equal to or less than the upper limit, sufficiently high coating stability can be ensured when the slurry composition is applied to a substrate to form a functional layer.

[0226] <<Surfactant>>

[0227] Furthermore, from the viewpoint of improving the coating property of the slurry composition, it is preferred to use a surfactant as another component. As the surfactant, there is no particular limitation, and for example, a polyethylene glycol-type surfactant can be used. In addition, the surfactant is a component different from the above-mentioned viscosity modifier (water-soluble polymer, etc.) and dispersant.

[0228] The amount of the surfactant in the slurry composition is not particularly limited. The amount of the surfactant in the slurry composition is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, preferably 0.5 parts by mass or less, and more preferably 0.3 parts by mass or less, based on solid content relative to 100 parts by mass of the functional particles.

[0229] When the amount of the surfactant in the slurry composition is not less than the above lower limit, the coating properties of the slurry composition on the substrate can be sufficiently ensured.

[0230] On the other hand, when the amount of the surfactant in the slurry composition is not more than the above upper limit, sufficiently high adhesion of the functional layer can be ensured.

[0231] <Solid content of slurry composition for secondary battery functional layer>

[0232] The solid content (particulate polymer, functional particles, other components, etc.) of the slurry composition is preferably 20 mass % or more, more preferably 30 mass % or more, and is preferably 60 mass % or less, more preferably 50 mass % or less.

[0233] When the solid content of the slurry composition is within the above range, the viscosity of the slurry composition can be appropriately maintained, thereby improving coating stability.

[0234] <Preparation of slurry composition for secondary battery functional layer>

[0235] The method for preparing the slurry composition is not particularly limited.

[0236] For example, when the slurry composition is a slurry composition for a porous membrane layer, the slurry composition can be prepared by mixing a binder, non-conductive particles, and other components used as necessary in the presence of a solvent.

[0237] In addition, as the solvent used in preparing the slurry composition, the solvent (such as water, etc.) mentioned above in the item "binder for secondary battery functional layer" can be used. In addition, the solvent used in preparing the slurry composition also includes the solvent contained in the binder. Moreover, the mixing method is not particularly limited, and mixing is performed using a commonly used stirrer or disperser.

[0238] (Functional layer for secondary battery)

[0239] The functional layer of the present invention is a layer that bears the functions of reinforcement or bonding in the secondary battery. As the functional layer, for example, a porous film layer that improves heat resistance and strength can be cited. Moreover, the functional layer of the present invention is formed by the above-mentioned slurry composition of the present invention, for example, it can be formed by drying the formed film after the above-mentioned slurry composition is applied to the surface of a suitable substrate. That is, the functional layer of the present invention is composed of the dried product of the above-mentioned slurry composition, usually containing at least granular polymers and functional particles, and arbitrarily further containing other components. In addition, each component included in the functional layer is each component included in the above-mentioned slurry composition, and therefore, the preferred existence ratio of these each component is the same as the preferred existence ratio of each component in the slurry composition.

[0240] Furthermore, since the functional layer of the present invention is formed from the slurry composition of the present invention containing the binder of the present invention, it has excellent heat shrinkage resistance, adhesion and storage stability.

[0241] <Base material>

[0242] Here, the substrate to which the slurry composition is applied is not limited. For example, a coating film of the slurry composition can be formed on the surface of a release substrate, the coating film is dried to form a functional layer, and the release substrate is peeled off from the functional layer. In this way, the functional layer peeled off from the release substrate can also be used as a self-supporting film to form a battery component of a secondary battery.

[0243] However, from the viewpoint of omitting the step of peeling off the functional layer and improving the manufacturing efficiency of the battery component, it is preferred to use a separator substrate or an electrode substrate as the substrate. Specifically, it is preferred to form the functional layer by applying the slurry composition on a separator substrate or an electrode substrate.

[0244] Furthermore, from the viewpoint of improving the adhesion between the formed functional layer and a substrate such as a separator substrate and an electrode substrate, the surface of the substrate may be subjected to a surface treatment such as a corona treatment or a plasma treatment to be hydrophilic.

[0245] <<Spacer base material>>

[0246] The spacer substrate is not particularly limited, and known spacer substrates such as organic spacer substrates can be cited. The organic spacer substrate is a porous member composed of an organic material. When citing examples of organic spacer substrates, microporous films or nonwoven fabrics containing polyolefin resins such as polyethylene and polypropylene, aromatic polyamide resins, etc. can be cited. From the viewpoint of excellent strength, microporous films and nonwoven fabrics made of polyethylene are preferred.

[0247] <<Electrode base material>>

[0248] The electrode substrate (positive electrode substrate and negative electrode substrate) is not particularly limited, and examples thereof include an electrode substrate in which an electrode composite material layer including electrode active material particles and a binder is formed on a current collector.

[0249] As the current collector, a material having conductivity and electrochemical durability can be used. Specifically, as the current collector, for example, a current collector composed of iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. can be used. Among them, as the current collector used in the negative electrode, copper foil is particularly preferred. In addition, as the current collector used in the positive electrode, aluminum foil is particularly preferred. In addition, the above-mentioned materials can be used alone or in combination of two or more in any ratio.

[0250] The electrode active material particles included in the electrode composite material layer in the electrode substrate are not particularly limited, and known electrode active material particles can be used. In addition, the binding material included in the electrode composite material layer as the electrode substrate can be any binding material used as the electrode composite material layer.

[0251] <Method for forming functional layer for secondary battery>

[0252] As a method for forming a functional layer on the above-mentioned substrate such as the separator substrate and the electrode substrate, the following method can be mentioned.

[0253] 1) A method of applying the slurry composition of the present invention on the surface of a substrate (in the case of an electrode substrate, the surface on the side of the electrode composite material layer, the same below), and then drying;

[0254] 2) A method of drying a substrate after immersing the substrate in the slurry composition of the present invention; and

[0255] 3) A method in which the slurry composition of the present invention is applied onto a release substrate and dried to produce a functional layer, and the obtained functional layer is transferred to the surface of the substrate.

[0256] Among these, the method 1) is particularly preferred because it is easy to control the thickness of the functional layer. In detail, the method 1) includes: a step of applying the slurry composition on a substrate (coating step); and a step of drying the slurry composition applied on the substrate to form a functional layer (drying step).

[0257] <<Coating process>>

[0258] In the coating step, the method for coating the slurry composition on the substrate is not particularly limited, and examples thereof include doctor blade method, reverse roll method, direct roll method, gravure printing method, extrusion method, brush coating method and the like.

[0259] <<Drying process>>

[0260] In addition, in the drying process, the method for drying the slurry composition on the substrate is not particularly limited, and a known method can be used. Examples of the drying method include: drying using warm air, hot air, and low-humidity air; vacuum drying; and drying using irradiation of infrared rays, electron beams, and the like. The drying conditions are not particularly limited, but the drying temperature is preferably 40° C. to 150° C., and the drying time is preferably 2 minutes to 30 minutes.

[0261] The thickness of the formed functional layer is preferably 1 μm or more, more preferably 1.5 μm or more, and is preferably 4 μm or less, more preferably 3 μm or less.

[0262] When the thickness of the functional layer is not less than the above lower limit, sufficiently high heat shrinkage resistance of the functional layer can be ensured.

[0263] On the other hand, when the thickness of the functional layer is equal to or less than the upper limit, the internal resistance of the secondary battery can be reduced by reducing the thickness of the functional layer, and as a result, the cycle characteristics of the secondary battery can be improved.

[0264] (Battery member having a functional layer for secondary battery)

[0265] Here, the battery component (separator and electrode) formed with the functional layer may also have the constituent elements other than the functional layer and substrate of the present invention as long as it does not significantly damage the effect of the present invention. As such constituent elements, it is not particularly limited, and porous membrane layers that do not belong to the functional layer of the present invention can be cited. In addition, as a layer that does not belong to the functional layer of the present invention, for example, a layer that does not include functional particles but contains the above-mentioned granular polymer and any other components, i.e., a so-called adhesive layer, can also be cited.

[0266] The battery member having the functional layer of the present invention is excellent in heat shrinkage resistance, adhesion and storage stability, and can be well adhered to an adjacent battery member.

[0267] (Secondary battery)

[0268] The secondary battery of the present invention has the above-mentioned functional layer of the present invention. More specifically, the secondary battery of the present invention has a positive electrode, a negative electrode, a separator and an electrolyte, and the above-mentioned functional layer for secondary battery is contained in at least one of the positive electrode, the negative electrode and the separator as battery components.

[0269] In addition, since the secondary battery of the present invention has the functional layer of the present invention that has excellent heat shrinkage resistance, adhesion and storage stability, the heat shrinkage rate caused by temperature changes is low, the battery components are well bonded to each other, and the heat shrinkage resistance and adhesion are not easily reduced even after a long time. Therefore, the battery characteristics such as cycle characteristics are excellent.

[0270] <Positive electrode, negative electrode and separator>

[0271] At least one of the positive electrode, negative electrode and separator used in the secondary battery of the present invention is a battery component having the functional layer of the present invention. In addition, there is no particular limitation on the positive electrode, negative electrode and separator not having the functional layer of the present invention, and known positive electrodes, negative electrodes and separators can be used.

[0272] <Electrolyte>

[0273] As the electrolyte, an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent can generally be used. As a supporting electrolyte, for example, a lithium salt can be used in a lithium ion secondary battery. As a lithium salt, for example, LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)2NLi, etc. can be cited. Among them, because it is easy to dissolve in a solvent and shows a high degree of dissociation, LiPF6, LiClO4, and CF3SO3Li are preferred. In addition, the electrolyte can be used alone or in combination of two or more. Generally, there is a tendency that the higher the degree of dissociation of the supporting electrolyte, the higher the lithium ion conductivity. Therefore, the lithium ion conductivity can be adjusted according to the type of supporting electrolyte.

[0274] As an organic solvent used in the electrolyte, there is no particular limitation as long as it can dissolve the supporting electrolyte. For example, in lithium-ion secondary batteries, carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), ethyl methyl carbonate (EMC), and vinylene carbonate (VC) can be appropriately used; esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as cyclopentane and dimethyl sulfoxide, etc. In addition, a mixed solution of these solvents can also be used. Among them, carbonates are preferred because of their high dielectric constant and wide stable potential region. Generally, there is a tendency that the lower the viscosity of the solvent used, the higher the lithium ion conductivity. Therefore, the lithium ion conductivity can be adjusted according to the type of solvent.

[0275] In addition, the concentration of the electrolyte in the electrolytic solution can be appropriately adjusted. In addition, a known additive may be added to the electrolytic solution.

[0276] <Method for producing secondary battery>

[0277] The secondary battery of the present invention described above can be manufactured, for example, by overlapping the positive electrode and the negative electrode with a spacer, winding and folding them as needed, placing them in a battery container, injecting electrolyte into the battery container and sealing them. In addition, at least one component of the positive electrode, the negative electrode, and the spacer can be used as a battery component having a functional layer of the present invention. In addition, porous metal mesh, fuses, PTC components and other overcurrent protection components, guide plates, etc. can also be placed in the battery container as needed to prevent the pressure inside the battery from rising and overcharging and discharging. The shape of the battery can be, for example, any one of a coin shape, a button shape, a sheet shape, a cylindrical shape, a square shape, a flat shape, etc.

[0278] Example

[0279] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. In addition, in the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified.

[0280] In addition, in a polymer produced by copolymerizing multiple monomers, the proportion of a repeating unit (monomer unit) formed by polymerizing a certain monomer in the above polymer is usually consistent with the ratio (charge ratio) of the certain monomer in all monomers used for polymerization of the polymer unless otherwise specified.

[0281] In the Examples and Comparative Examples, the measurement and evaluation of various properties were carried out according to the following methods.

[0282] <Volume average particle size of granular polymer>

[0283] The volume average particle size of the particulate polymer is measured by laser diffraction.

[0284] Specifically, first, the prepared aqueous dispersion containing the particulate polymer (the solid content is adjusted to 0.1% by mass) is used as a sample. Then, in the particle size distribution (volume basis) measured using a laser diffraction particle size distribution measuring device (manufactured by Beckman Coulter, product name "LS-13320"), the particle size D50 at which the cumulative volume calculated from the small particle size side becomes 50% is used as the volume average particle size.

[0285] <Glass transition temperature of granular polymer>

[0286] The prepared dispersion containing the particulate polymer was pre-dried for 3 days under a relative humidity of 50% and a temperature of 23 to 26°C to form a pre-film with a thickness of 2±0.5 mm. The pre-film was dried in a vacuum dryer at a temperature of 120°C for 10 hours. After that, the dried film was used as a sample, and the glass transition temperature (°C) was measured using a differential scanning calorimeter (DSC7200, manufactured by SII Corporation) under the conditions of a measurement temperature of -100°C to 180°C and a heating rate of 5°C / min in accordance with JIS K7121.

[0287] <Electrolyte swelling degree>

[0288] The prepared aqueous dispersion containing the granular polymer is dried under a relative humidity of 50% and a temperature of 23 to 25°C to form a film with a thickness of about 0.1 mm. The formed film is cut into about 2 cm squares and the weight (weight before immersion) is measured. After that, it is immersed in an electrolyte at a temperature of 60°C for 72 hours. The immersed film is pulled up, the electrolyte is wiped off, and the weight (weight after immersion) is immediately measured, and the value of (weight after immersion) / (weight before immersion)×100(%) is used as the swelling degree of the electrolyte. In addition, as an electrolyte, a solution obtained by dissolving LiPF6 at a concentration of 1 mol / L in a mixed solvent of 3:7 (weight ratio) of ethylene carbonate and ethyl methyl carbonate is used.

[0289] <Measurement of pH of adhesive>

[0290] The pH of the prepared aqueous dispersion (binder) containing the particulate polymer was measured at 25° C. using a pH meter F-21 manufactured by Horiba, Ltd. after calibrating a glass electrode with buffer solutions of pH 4, pH 7, and pH 9.

[0291] <Elastic modulus of film composed of granular polymer after accelerated test>

[0292] The prepared aqueous dispersion containing the granular polymer was left to stand at 60°C for 14 days and subjected to an accelerated test. The film was made by air-drying the aqueous dispersion containing the granular polymer after the accelerated test at a relative humidity of 50% and a temperature of 25°C. The obtained film was passed through a slicer to obtain 2 μm slices. For the obtained slices, the film elastic modulus was measured in the FV mode of an atomic force microscope (AFM). The median of the measurement results was used as the evaluation result. In addition, as a device (atomic force microscope), a device named "FastScan" manufactured by Bruker was used.

[0293] <Elastic modulus of film composed of granular polymer before accelerated test>

[0294] The film is made by air-drying the aqueous dispersion containing the granular polymer before the above-mentioned accelerated test at a relative humidity of 50% and a temperature of 25°C. The obtained film is passed through a slicer to obtain a 2 μm slice. For the obtained slice, the film elastic modulus is measured in the FV mode of an atomic force microscope (AFM). The median of the measurement result is used as the evaluation result. In addition, as an apparatus (atomic force microscope), a device called "FastScan" made by Bruker Corporation is used.

[0295] <Adhesion of functional layer for secondary battery>

[0296] The separators with functional layers produced in Examples and Comparative Examples were cut into pieces with a width of 10 mm and a length of 50 mm to prepare test pieces.

[0297] Next, a stainless steel plate with a double-sided tape (Nitto Denko, No. 5608) attached was prepared, and the functional layer surface of the test piece was attached to the double-sided tape. Then, the strength when one end of the spacer substrate was stretched and peeled at a speed of 50 mm / min in a manner such that the peeling surface became 180° was measured, and the adhesion of the functional layer was evaluated according to the following criteria. The greater the peel strength, the better the adhesion.

[0298] A: Peel strength is 15N / m or more

[0299] B: Peel strength is 5 N / m or more and less than 15 N / m

[0300] C: Peel strength less than 5N / m

[0301] <Heat shrinkage resistance of functional layer for secondary battery>

[0302] The spacers with functional layers prepared in the examples and comparative examples were cut into squares with a side of 12 cm, and a square with a side of 10 cm was drawn inside the square as a test piece. Then, after the test piece was placed in a constant temperature bath at 150°C for 1 hour, the area change of the square drawn inside (=[(area of ​​the square before placement - area of ​​the square after placement) / area of ​​the square before placement] × 100%) was calculated as the heat shrinkage rate, and evaluated according to the following criteria. The smaller the heat shrinkage rate, the better the heat shrinkage resistance of the functional layer.

[0303] A: Thermal shrinkage is less than 10%

[0304] B: Thermal shrinkage is 10% or more and less than 20%

[0305] C: Thermal shrinkage is more than 20%

[0306] <Storage stability of secondary battery functional layer>

[0307] The spacers with functional layers prepared in the examples and comparative examples were left standing in a thermostatic chamber at 40°C for 90 days. Thereafter, the adhesion and heat shrinkage resistance of the spacers with functional layers were measured in the same procedure as above, and the adhesion and heat shrinkage resistance of the functional layers after standing for 90 days were evaluated according to the same criteria as above. Then, the evaluation results of the adhesion and heat shrinkage resistance before standing for 90 days (i.e., the evaluation results of the "adhesion" and "heat shrinkage resistance" described above) were compared with the evaluation results of the adhesion and heat shrinkage resistance after standing for 90 days, and the evaluation was performed according to the following criteria.

[0308] A: There is no change in the evaluation results of adhesion and heat shrinkage resistance before and after 90 days of standing.

[0309] B: After standing for 90 days, the evaluation results of either adhesion or heat shrinkage resistance decreased by one level

[0310] C: Before and after 90 days of standing, the evaluation results of both adhesion and heat shrinkage resistance decreased by one level, or before and after 90 days of standing, the evaluation results of either adhesion or heat shrinkage resistance decreased by two levels.

[0311] <Cycle characteristics of secondary batteries>

[0312] The prepared lithium ion secondary battery was left to stand for 24 hours at 25°C. After that, the battery was charged to 4.2V (cut-off condition: 0.02C) at a charge rate of 1C by constant voltage and constant current (CC-CV) method at 25°C, and discharged to 3.0V by constant current (CC) method at a discharge rate of 1C, and the initial capacity C0 was measured.

[0313] Furthermore, the same charge and discharge operation was repeated under a 25°C environment, and the capacity C1 after 300 cycles was measured. Then, the capacity retention rate ΔC = (C1 / C0) × 100 (%) was calculated and evaluated according to the following criteria. The higher the value of the capacity retention rate, the less the decrease in discharge capacity and the better the cycle characteristics.

[0314] A: Capacity retention rate ΔC is more than 85%

[0315] B: Capacity retention rate ΔC is 75% or more and less than 85%

[0316] C: Capacity retention rate ΔC is less than 75%

[0317] (Example 1)

[0318] <Preparation of aqueous dispersion (binder) containing particulate polymer>

[0319] Into a reactor equipped with a stirrer, 90 parts of ion exchange water, 0.05 parts of sodium dodecylbenzenesulfonate (Neopelex G-15, manufactured by Kao Chemical Co., Ltd.) as an emulsifier, and 0.23 parts of ammonium persulfate as a polymerization initiator were respectively supplied, the gas phase was replaced with nitrogen, and the temperature was raised to 70°C.

[0320] On the other hand, in another container, 50 parts of ion exchange water, 0.2 parts of sodium dodecylbenzenesulfonate (Kao Chemical Co., Ltd., "Neopelex G-15") as an emulsifier, 70 parts of butyl acrylate (BA) as a (meth)acrylate monomer, 10 parts of acrylonitrile (AN) as a cyano group-containing monomer, 17.8 parts of allyl glycidyl ether (AGE) as a reactive functional group-containing monomer, and 2 parts of N-hydroxymethyl acrylamide (NMA), and 0.2 parts of acrylic acid (AA) as an acidic functional group-containing monomer were mixed to obtain a monomer composition. The monomer composition was continuously added to the above reactor over 3 hours to perform polymerization. The reaction was performed at 70° C. during the addition. After the addition was completed, the reaction solution was cooled to 50°C, 0.2 parts of tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF Corporation, product name "Perbutyl O") as a polymerization initiator was added, and 0.1 parts of ascorbic acid as a reducing agent were added, and the reaction was completed by stirring for 3 hours to produce an aqueous dispersion (binder) containing a granular polymer. The pH of the obtained binder was adjusted to 6 using 10% ammonia water. In addition, the solid content of the binder was 40%. Various properties of the obtained binder were measured. The results are shown in Table 1.

[0321] <Preparation of slurry composition>

[0322] In the preparation of the slurry composition, alumina particles (AKP-3000 manufactured by Sumitomo Chemical, volume average particle size D50 = 0.7 μm) were used as non-conductive particles (functional particles), acrylic acid / sulfonic acid monomer copolymer sodium salt (manufactured by Nippon Shokubai Co., Ltd., product name "AQUALIC GL366") was used as a dispersant, carboxymethyl cellulose with an etherification degree of 0.8 to 1.0 (manufactured by Daicel Fine Chemicals Co., Ltd., product name "1220") was used as a viscosity modifier, and a polyethylene glycol type surfactant (manufactured by San Nopco, NOPTEX ED-052) was used as a surfactant. In addition, the viscosity of a 1% aqueous solution of the viscosity modifier is 10 to 20 mPa·s.

[0323] First, 100 parts of non-conductive particles and 0.5 parts of a dispersant were mixed with ion exchange water and treated with a bead mill (LMZ015 manufactured by Ashizawa Meiji Technology Co., Ltd.) for 1 hour to obtain a dispersion. Furthermore, 3 parts of an aqueous dispersion containing a particulate polymer in terms of solid content, 1.5 parts of a 4% aqueous solution of carboxymethyl cellulose in terms of solid content, and 0.2 parts of a polyethylene glycol-type surfactant were mixed to prepare a slurry composition having a solid content of 40% by mass.

[0324] <Production of a spacer having a functional layer on one side>

[0325] A polyethylene spacer substrate (manufactured by Asahi Kasei Corporation, trade name "ND412", thickness: 12 μm) was prepared. The slurry composition prepared above was applied to the surface of the prepared spacer substrate, and dried at a temperature of 50°C for 3 minutes to obtain a spacer having a functional layer on one side (thickness of the functional layer: 3 μm). The obtained spacer with a functional layer was used to evaluate adhesion, heat shrinkage resistance and storage stability. The results are shown in Table 1.

[0326] <Production of negative electrode>

[0327] 33 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, 3.5 parts of itaconic acid as a carboxylic acid group-containing monomer, 63.5 parts of styrene as an aromatic vinyl monomer, 0.4 parts of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts of ion exchange water and 0.5 parts of potassium persulfate as a polymerization initiator were added to a 5MPa pressure-resistant container with a stirrer. After sufficient stirring, the solution was heated to 50°C to initiate polymerization. When the polymerization conversion rate reached 96%, the polymerization reaction was terminated by cooling to obtain a mixture containing a granular binder (styrene-butadiene copolymer). A 5% sodium hydroxide aqueous solution was added to the mixture, and after adjusting the pH to 8, the unreacted monomers were removed by heating and reduced pressure distillation. After that, the mixture after the unreacted monomers were removed was cooled to below 30°C to obtain an aqueous dispersion containing a binder material for the negative electrode.

[0328] 48.75 parts of artificial graphite (theoretical capacity: 360 mAh / g) as the negative electrode active material, 48.75 parts of natural graphite (theoretical capacity: 360 mAh / g), and 1 part of carboxymethyl cellulose as a thickener were added to the planetary mixer. Furthermore, the solid content was diluted to 60% with ion exchange water, and then kneaded at a speed of 45 rpm for 60 minutes. After that, 1.5 parts of the above-mentioned aqueous dispersion containing the negative electrode binder material was added in an equivalent amount of solid content, and kneaded at a speed of 40 rpm for 40 minutes. Then, ion exchange water was added in such a way that the viscosity became 3000±500 mPa・s (B-type viscometer, measured at 25°C and 60 rpm) to prepare a slurry composition for the negative electrode composite material layer.

[0329] The negative electrode composite material layer slurry composition was coated with a notch wheel coater at a coating amount of 11±0.5 mg / cm 2 The copper foil having a thickness of 15 μm was coated on the surface of the current collector. After that, the copper foil coated with the slurry composition for the negative electrode composite material layer was conveyed in an oven at a temperature of 80°C for 2 minutes at a speed of 400 mm / min, and further conveyed in an oven at a temperature of 110°C for 2 minutes, thereby drying the slurry composition on the copper foil to obtain a negative electrode raw material having a negative electrode composite material layer formed on the current collector.

[0330] Then, the negative electrode material layer side of the negative electrode material was rolled at a temperature of 25±3°C and a linear pressure of 11 t (tons) to obtain a negative electrode material layer with a density of 1.60 g / cm 3 Then, the negative electrode was placed in an environment with a temperature of 25±3°C and a relative humidity of 50±5% for 1 week.

[0331] <Production of positive electrode>

[0332] 96 parts of Co-Ni-Mn lithium composite oxide active material NMC111 (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2), 2 parts of acetylene black (manufactured by Denki Kagaku Kogyo Co., Ltd., trade name "HS-100") as a conductive material, 2 parts of polyvinylidene fluoride (manufactured by Kureha Chemical, trade name "KF-1100") as a binder, and further N-methyl-2-pyrrolidone (NMP) as a dispersion medium was added and mixed in such a manner that the total solid content became 67% to prepare a slurry composition for a positive electrode composite material layer.

[0333] Next, the obtained positive electrode composite material layer slurry composition was coated with a notch wheel coater so that the coating amount became 20±0.5 mg / cm 2 The molten-salt aluminum foil was coated on a 20 μm thick aluminum foil as a current collector.

[0334] The slurry composition on the aluminum foil was dried by conveying it in an oven at 90°C for 2 minutes at a speed of 200 mm / min and further in an oven at 120°C for 2 minutes to obtain a positive electrode raw material having a positive electrode composite material layer formed on the current collector.

[0335] Then, the positive electrode material layer side of the prepared positive electrode raw material was roll-pressed at a temperature of 25±3°C and a linear pressure of 14 t (tons) to obtain a positive electrode material layer density of 3.40 g / cm 3 Thereafter, the positive electrode was placed in an environment of a temperature of 25±3°C and a relative humidity of 50±5% for 1 week.

[0336] <Manufacturing of secondary batteries>

[0337] The pressed positive electrode obtained above was cut into a square of 4cm×4cm, and the pressed negative electrode was cut into 4.2cm×4.2cm. In addition, the functional layer separator with a functional layer obtained above was cut into 5cm×5cm. Next, the functional layer coating surface of the cut separator with a functional layer was arranged toward the positive electrode composite material layer of the cut pressed positive electrode. Furthermore, the cut pressed negative electrode composite material layer was arranged toward the surface of the separator with a functional layer that was not in contact with the positive electrode, and a battery component stack (positive electrode / functional layer / separator substrate / negative electrode) was obtained. Next, the obtained stack was packaged with an aluminum packaging material outer packaging as an outer packaging of the battery, and the electrolyte (solvent: ethylene carbonate (EC) / diethyl carbonate (DEC) / vinyl carbonate (VC) (volume ratio = 68.5 / 30 / 1.5), electrolyte: LiPF6 with a concentration of 1 mol / L) was injected in a manner that no air was left. Then, the opening of the aluminum packaging material outer package was heat-sealed at a temperature of 150° C., and the aluminum packaging material outer package was hermetically sealed to produce a 40 mAh laminated lithium ion secondary battery. The cycle characteristics were evaluated using the lithium ion secondary battery. The results are shown in Table 1.

[0338] (Example 2)

[0339] The various operations, measurements, and evaluations were carried out in the same manner as in Example 1 except that methacrylic acid was used to obtain a monomer composition in the preparation of the aqueous dispersion containing the particulate polymer.

[0340] (Example 3)

[0341] The various operations, measurements and evaluations were carried out in the same manner as in Example 2 except that allyl glycidyl ether as the reactive functional group-containing monomer was replaced with glycidyl methacrylate to obtain a monomer composition in the preparation of the aqueous dispersion containing the particulate polymer.

[0342] (Example 4)

[0343] The various operations, measurements, and evaluations were carried out in the same manner as in Example 3 except that methacrylonitrile was used to obtain a monomer composition in the preparation of the aqueous dispersion containing the particulate polymer.

[0344] (Example 5)

[0345] In the preparation of the aqueous dispersion containing the particulate polymer, 0.2 parts of sodium dodecylbenzenesulfonate ("Neopelex G-15" manufactured by Kao Chemical Co., Ltd.) as an emulsifier, 70 parts of butyl acrylate as a (meth)acrylate monomer, 10 parts of acrylonitrile as a cyano group-containing monomer, 18 parts of allyl glycidyl ether and 1.4 parts of N-methylol acrylamide as a reactive functional group-containing monomer, 0.2 parts of methacrylic acid as an acidic functional group-containing monomer, and 0.4 parts of ethylene glycol dimethacrylate as a crosslinking monomer were mixed to obtain a monomer composition, and various operations, measurements, and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1.

[0346] (Example 6)

[0347] In the preparation of the aqueous dispersion containing the particulate polymer, various operations, measurements and evaluations were carried out in the same manner as in Example 5, except that allyl glycidyl ether as the reactive functional group-containing monomer was replaced with glycidyl methacrylate, and ethylene glycol dimethacrylate as the crosslinking monomer was replaced with allyl methacrylate to obtain a monomer composition. The results are shown in Table 1.

[0348] (Example 7)

[0349] In the preparation of the aqueous dispersion containing the particulate polymer, the various operations, measurements and evaluations were carried out in the same manner as in Example 6, except that the amount of butyl acrylate as the (meth)acrylate monomer was changed to 53 parts, and the amount of acrylonitrile as the cyano group-containing monomer was changed to 27 parts to obtain a monomer composition. The results are shown in Table 1.

[0350] (Example 8)

[0351] In the preparation of the aqueous dispersion containing the particulate polymer, various operations, measurements and evaluations were carried out in the same manner as in Example 6, except that the amount of butyl acrylate as the (meth)acrylate monomer was changed to 76 parts, and the amount of acrylonitrile as the cyano group-containing monomer was changed to 4 parts to obtain a monomer composition. The results are shown in Table 1.

[0352] (Example 9)

[0353] In the preparation of the aqueous dispersion containing the particulate polymer, the various operations, measurements and evaluations were carried out in the same manner as in Example 6, except that the amount of butyl acrylate as the (meth)acrylate monomer was changed to 60 parts, and the amount of glycidyl methacrylate as the reactive functional group-containing monomer was changed to 28 parts to obtain a monomer composition. The results are shown in Table 1.

[0354] (Example 10)

[0355] In the preparation of the aqueous dispersion containing the particulate polymer, the various operations, measurements and evaluations were carried out in the same manner as in Example 6, except that the amount of butyl acrylate as the (meth)acrylate monomer was changed to 80 parts, and the amount of glycidyl methacrylate as the reactive functional group-containing monomer was changed to 8 parts to obtain a monomer composition. The results are shown in Table 1.

[0356] (Example 11)

[0357] In the preparation of the aqueous dispersion containing the particulate polymer, the monomer composition was obtained by changing the amount of N-methylol acrylamide as the reactive functional group-containing monomer to 0.9 parts, the amount of methacrylic acid as the acidic functional group-containing monomer to 0.8 parts, and the amount of allyl methacrylate as the crosslinking monomer to 0.3 parts. Various operations, measurements, and evaluations were carried out in the same manner as in Example 6. The results are shown in Table 1.

[0358] (Example 12)

[0359] In the preparation of the aqueous dispersion containing the particulate polymer, various operations, measurements and evaluations were carried out in the same manner as in Example 6, except that the amount of methacrylic acid as the acidic functional group-containing monomer was changed to 0.1 parts, and the amount of allyl methacrylate as the crosslinking monomer was changed to 0.5 parts to obtain a monomer composition. The results are shown in Table 1.

[0360] (Example 13)

[0361] In the preparation of the aqueous dispersion containing the particulate polymer, the various operations, measurements and evaluations were carried out in the same manner as in Example 6, except that the amount of butyl acrylate as the (meth)acrylate monomer was changed to 67.8 parts, the amount of N-methylol acrylamide as the reactive functional group-containing monomer was changed to 3 parts, and the amount of allyl methacrylate as the crosslinking monomer was changed to 1 part to obtain a monomer composition. The results are shown in Table 1.

[0362] (Example 14)

[0363] In the preparation of the aqueous dispersion containing the particulate polymer, the monomer composition was obtained by changing the amount of butyl acrylate as the (meth)acrylate monomer to 71.1 parts, the amount of N-methylol acrylamide as the reactive functional group-containing monomer to 0.5 parts, and the amount of allyl methacrylate as the crosslinking monomer to 0.2 parts. Various operations, measurements, and evaluations were carried out in the same manner as in Example 6. The results are shown in Table 1.

[0364] (Example 15)

[0365] The various operations, measurements, and evaluations were carried out in the same manner as in Example 6, except that the pH was adjusted to 4.5 in the preparation of the aqueous dispersion containing the particulate polymer.

[0366] (Example 16)

[0367] The various operations, measurements, and evaluations were carried out in the same manner as in Example 6, except that the pH was adjusted to 7.5 in the preparation of the aqueous dispersion containing the particulate polymer.

[0368] (Example 17)

[0369] In the preparation of the aqueous dispersion containing the particulate polymer, the amount of the emulsifier previously added to the reactor was changed from 0.05 parts to 0 parts (i.e., no emulsifier was added to the reactor) to adjust the volume average particle size of the particulate polymer to 0.18 μm, and various operations, measurements and evaluations were carried out in the same manner as in Example 6. The results are shown in Table 1.

[0370] (Example 18)

[0371] In the preparation of the aqueous dispersion containing the particulate polymer, the various operations, measurements and evaluations were carried out in the same manner as in Example 6, except that the amount of the emulsifier previously added to the reactor was changed from 0.05 parts to 0.1 parts so that the volume average particle size of the particulate polymer was adjusted to 0.12 μm. The results are shown in Table 1.

[0372] (Example 19)

[0373] In the preparation of the slurry composition, various operations, measurements and evaluations were carried out in the same manner as in Example 6 except that the alumina particles as the non-conductive particles were changed to boehmite (APYRAL AOH60 manufactured by Nabhot, volume average particle size D50=0.9 μm).

[0374] (Example 20)

[0375] In the preparation of the slurry composition, various operations, measurements and evaluations were carried out in the same manner as in Example 6 except that the alumina particles as the non-conductive particles were changed to barium sulfate (TS-3 manufactured by Takehara Chemical, volume average particle size D50 = 0.6 μm).

[0376] (Example 21)

[0377] In the preparation of the slurry composition, various operations, measurements, and evaluations were carried out in the same manner as in Example 6, except that carboxymethylcellulose as a viscosity modifier was changed to anionic polyacrylamide (Polystron 117, manufactured by Arakawa Chemical Industries, Ltd.).

[0378] (Comparative Example 1)

[0379] In the preparation of the aqueous dispersion containing the particulate polymer, the various operations, measurements and evaluations were carried out in the same manner as in Example 6, except that the amount of butyl acrylate as the (meth)acrylate monomer was changed to 50 parts, and the amount of allyl glycidyl ether as the reactive functional group-containing monomer was changed to 38 parts to obtain a monomer composition. The results are shown in Table 1.

[0380] (Comparative Example 2)

[0381] In the preparation of the aqueous dispersion containing the particulate polymer, 0.2 parts of sodium dodecylbenzenesulfonate ("Neopelex G-15" manufactured by Kao Chemical Co., Ltd.) as an emulsifier, 93.6 parts of butyl acrylate as a (meth)acrylate monomer, 2 parts of acrylonitrile as a cyano group-containing monomer, 2 parts of allyl glycidyl ether as a reactive functional group-containing monomer, 2 parts of methacrylic acid as an acidic functional group-containing monomer, and 0.4 parts of ethylene glycol dimethacrylate as a crosslinking monomer were mixed to obtain a monomer composition, and various operations, measurements, and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1.

[0382] (Comparative Example 3)

[0383] In the preparation of the aqueous dispersion containing the particulate polymer, the monomer composition was obtained by changing the amount of butyl acrylate as the (meth)acrylate monomer to 77.6 parts, the amount of acrylonitrile as the cyano group-containing monomer to 10 parts, and the amount of allyl glycidyl ether as the reactive functional group-containing monomer to 10 parts. Various operations, measurements, and evaluations were carried out in the same manner as in Comparative Example 2. The results are shown in Table 1.

[0384] (Comparative Example 4)

[0385] In the preparation of the aqueous dispersion containing the particulate polymer, 0.2 parts of sodium dodecylbenzenesulfonate ("Neopelex G-15" manufactured by Kao Chemical Co., Ltd.) as an emulsifier, 70 parts of butyl acrylate as a (meth)acrylate monomer, 10 parts of acrylonitrile as a cyano group-containing monomer, and 18 parts of glycidyl methacrylate and 2 parts of N-methylol acrylamide as a reactive functional group-containing monomer were mixed to obtain a monomer composition. Various operations, measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1.

[0386] (Comparative Example 5)

[0387] In the preparation of the aqueous dispersion containing the particulate polymer, the monomer composition was obtained by changing the amount of butyl acrylate as the (meth)acrylate monomer to 65.8 parts, the amount of N-methylol acrylamide as the reactive functional group-containing monomer to 4 parts, and the amount of allyl methacrylate as the crosslinking monomer to 2 parts. Various operations, measurements, and evaluations were carried out in the same manner as in Example 6. The results are shown in Table 1.

[0388] In addition, in Table 1 shown below,

[0389] "BA" represents butyl acrylate units,

[0390] "AN" stands for acrylonitrile unit,

[0391] "MAN" means methacrylonitrile unit,

[0392] "AA" represents acrylic acid unit,

[0393] "MAA" means methacrylic acid units,

[0394] "AGE" means allyl glycidyl ether unit,

[0395] "GMA" means glycidyl methacrylate units,

[0396] "NMA" means N-methylol acrylamide unit,

[0397] "EDMA" means ethylene glycol dimethacrylate units,

[0398] "AMA" means allyl methacrylate units,

[0399] "COO / SO3[Na]" means the sodium salt of acrylic acid / sulfonic acid monomer copolymer,

[0400] "CMC" stands for carboxymethyl cellulose,

[0401] "PAA" stands for polyacrylamide,

[0402] "PEG type" means that the surfactant is polyethylene glycol type.

[0403] The “elastic modulus after the accelerated test” means the elastic modulus of the film composed of the particulate polymer after the accelerated test.

[0404] “Elastic modulus before the accelerated test” means the elastic modulus of a film composed of a particulate polymer before the accelerated test.

[0405] [Table 1]

[0406] .

[0407] As can be seen from Table 1, when the adhesives of Examples 1 to 21 are used, a functional layer having excellent heat shrinkage resistance, adhesiveness, and storage stability can be formed.

[0408] Industrial Applicability

[0409] According to the present invention, it is possible to provide a binder for a secondary battery functional layer capable of forming a functional layer having excellent heat shrinkage resistance, adhesiveness, and storage stability.

[0410] Furthermore, according to the present invention, it is possible to provide a slurry composition for a secondary battery functional layer capable of forming a functional layer having excellent heat shrinkage resistance, adhesiveness, and storage stability.

[0411] Furthermore, according to the present invention, a functional layer for a secondary battery having excellent heat shrinkage resistance, adhesiveness, and storage stability can be provided.

[0412] Furthermore, according to the present invention, a secondary battery having the functional layer can be provided.

Claims

1. A binder for a secondary battery functional layer, comprising a granular polymer, The particulate polymer comprises an acidic functional group-containing monomer unit and a reactive functional group-containing monomer unit having a functional group capable of reacting with the acidic functional group. When all monomer units contained in the particulate polymer are taken as 100 mass %, the content ratio of the reactive functional group-containing monomer unit is 7 mass % or more and 30 mass % or less, The elastic modulus of the film composed of the particulate polymer after the accelerated test is 10 MPa or less.

2. The binder for a secondary battery functional layer according to claim 1, wherein: When all monomer units contained in the particulate polymer are taken as 100% by mass, the content ratio of the acidic functional group-containing monomer units is 0.1% by mass or more and 1% by mass or less.

3. The binder for a secondary battery functional layer according to claim 1 or 2, wherein: The particulate polymer further comprises a crosslinkable monomer unit, When all monomer units contained in the particulate polymer are taken as 100 mass %, the content ratio of the crosslinkable monomer unit is more than 0 mass % and 1.5 mass % or less.

4. The binder for a secondary battery functional layer according to any one of claims 1 to 3, wherein: The particulate polymer further comprises a cyano group-containing monomer unit, When all monomer units contained in the particulate polymer are taken as 100 mass %, the content ratio of the cyano group-containing monomer unit is 2 mass % or more and 30 mass % or less.

5. The binder for a secondary battery functional layer according to any one of claims 1 to 4, wherein The binder for a secondary battery functional layer contains water and has a pH of 4 or more and 8 or less.

6. The binder for a secondary battery functional layer according to any one of claims 1 to 5, wherein: The glass transition temperature of the particulate polymer is 20° C. or lower.

7. The binder for a secondary battery functional layer according to any one of claims 1 to 6, wherein: The volume average particle size of the particulate polymer is 0.1 μm or more and 0.2 μm or less.

8. The binder for a secondary battery functional layer according to any one of claims 1 to 7, wherein The electrolyte swelling degree of the particulate polymer is 3 times or more and 5 times or less. 9 . A slurry composition for a secondary battery functional layer, comprising functional particles and the binder for a secondary battery functional layer according to claim 1 .

10. The slurry composition for a secondary battery functional layer according to claim 9, wherein The functional particles include non-conductive particles.

11. The slurry composition for a secondary battery functional layer according to claim 10, wherein: A ratio of the volume average particle diameter of the non-conductive particles to the volume average particle diameter of the particulate polymer is 2.0 times or more and 7.0 times or less. 12 . A secondary battery functional layer formed using the slurry composition for a secondary battery functional layer according to claim 9 . 13 . A secondary battery comprising the functional layer for a secondary battery according to claim 12 .